THE EFFECT OF USING ELECTRICAL CONTROL TECHNIQUES SIMULATOR SOFTWARE MEDIA ON STUDENTS' LEARNING OUTCOMES IN THE SUBJECT OF ELECTRIC MOTOR INSTALLATION FOR GRADE XI STUDENTS OF ELECTRICAL POWER INSTALLATION ENGINEERING (TITL) AT STATE VOCATIONAL HIGH SCHOOL 5 MEDAN - Sukarman Purba; Yobelita Lastarda; Anggur Aris; Alfredo Kaban (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
The Electrical Control Techniques Simulator (EKTS) learning media serves as a solution to address challenges in the learning process and enhance students' motivation to learn. EKTS is a software simulator that facilitates the design of electronic systems with various electromechanical elements. However, its application is still limited in Vocational High Schools (SMK), despite the vital role SMK plays in human resource development. This research employs a quasi-experimental approach to examine the influence of EKTS learning media on students' learning outcomes in the subject of Electric Motor Installation. The experimental class (XI TITL 1) utilizes EKTS, while the control class (XI TITL 2) uses conventional media, namely chalkboards. The pretest results indicate that both classes initially had balanced scores. However, after the intervention, the posttest scores of the experimental class significantly surpassed those of the control class. The average learning outcomes of the experimental class students were 83.02, whereas those of the control class were 69.06. Student learning activities with EKTS are classified as active, indicating the effectiveness of this media in improving the quality of learning. These findings demonstrate that the use of EKTS learning media has an impact on students' learning outcomes in the Electric Motor Installation subject at SMK Negeri 5 Medan in the second semester of the academic year 2023/2024